Review of algebraic attacks on stream ciphers - ZHANG Long1; WU Wen-ling2; WEN Qiao-yan1 (Tongxin xuebao)
The basic theory and realizing methods of algebraic attacks on stream ciphers are presented.Then the algebraic attacks on stream ciphers with linear feedback shift register and the efficient techniques to decrease the degree of the nonlinear equations system are described in detail.After analyzing the complexity of whole procedures in algebraic attacks,the direction and future works of this research filed are summarized in the end.